COMPETENCE MANAGEMENT OF COTTON-TEXTILE CLUSTER EMPLOYEES - Tojiboeva Nafisakhon Rakhmiddin kizi (Journal Park Publishing, 2023)
In the years of independence, serious attention was paid to the further development of cotton-textile clusters in our republic, large-scale practical work is being done to attract foreign investments to the industry, to improve personnel qualifications, to create new jobs, and to apply innovative management methods. In the Strategy of Actions on the five priority directions of the development of the Republic of Uzbekistan in 2017-2021, "mastering new types of products and technologies and ensuring the competitiveness of national goods on the domestic and foreign markets on this basis" was defined as a priority. The successful implementation of these tasks requires the improvement of personnel management mechanisms in the development of the labor potential of the cotton-textile clusters of our republic. This article is about this.
Keywords: Cotton-textile clusters, quality, national goods, competitiveness, management, strategic management, business, labor potential.